Meeting between the Prime Minister and representatives of the Mining Association and Miners' Federation of Great Britain (verbatim report) : (1926/03/06) - Mining Association of Great Britain ; Miners' Federation of Great Britain ; Baldwin, Stanley Baldwin, Earl, 1867-1947
[6 March 1926?]